Influence of explant type and variety of Linum usitatissimum L. convar. elongatum on the intensity of callus formation and organogenesis in vitro - S. V. Mishchenko; L. M. Kryvosheeva; Yu. V. Lavrynenko; T. Yu. Marchenko (Plant Varieties Studying and Protection)
Purpose. To determine the dependence of the intensity of callus formation and organogenesis of Linum usitatissimum L. convar. elongatum in vitro on explant type and variety in order to optimize the cultivation protocol.